Competitividade, coesão social e qualidade ambiental: uma análise do desenvolvimento das microrregiões do estado do Paraná - Corte, Greice Morais Dalla (2019)
In the contemporary world, the quality of life has been a subject that has generated concern and debate in the various fields of society, whether in the scientific world, in organizations, in state planning, among others. The various scientific fields seek innovations, understanding, solutions and methods that help improve processes, relationships, clinical care and structures. Economic science in the area of socioeconomic development makes its contribution to these debates, and the evolution with the concern of development extends in the area of regional economy. The leading theorists of regional economics point out that economic developments occur in a variety of ways, from the location of capital, where it may or may not be attractive to capital itself, to the interrelationships that occur within particular localities and the relationships that it may have. locality has with other localities, where it may or may not be part of the territory. In addition, the historical process of economic consolidation of the regions interferes with longterm socioeconomic development. Brazil has undergone important processes in economic development and it is noticeable the differences in socioeconomic development between the major regions, as well as the differences in socio-economic development between the microregions of the state of Paraná. Thus, the general objective of this work is to measure the degree of socio-economic development of Parana's microregions (MGR) based on three pillars: competitiveness, social cohesion and environmental quality. In addition, the objective is to verify the differences in socio-economic development from the calculated index, and to verify whether these differences constitute a regional development problem, and to observe what is the relationship between the regional development processes (ISDR), using basic statistics. , followed by the qualitative discussion of the results obtained. The main results pointed out that the MGRs that are located at the extreme of the state territory, present better ISDR, just as the MGRs located in the central and northern areas of the state presented low rates of regional development